A practical guide to happiness in children and teens on the autism spectrum : a positive psychology approach - Honeybourne, Victoria (Language and communication teacher) (Jessica Kingsley Publishers, 2018)
"Bringing a refreshingly positive approach to mental health and autism, the guide is full of practical ideas for helping children strengthen their self-worth, optimism and receptivity to happiness. It also reveals how children can build resilience and better understand their feelings, giving them the skills to flourish and thrive and to ward off negative thoughts. The activities are ideal for all learning levels and can be done individually or in groups, at home or in the classroom."--Page 4 of cover